Social and sexual risk factors for bacterial vaginosis. Issue 1 (30th January 2004) - Smart, S; Singal, A; Mindel, A
Abstract : Background: A number of sexual and social risk factors for bacterial vaginosis (BV) have been identified. However, many previous studies have used small numbers of patients, or highly selected or convenience samples, or poorly defined populations. This study aims to clarify potential sexual and non-sexual risk factors for BV. Methods: Women attending the Sydney Sexual Health Centre with BV, between March 1991 and July 1999, were included. Controls were randomly selected women without BV. Information on the demographics, clinical findings, and sexual and non-sexual risk behaviours were extracted from the clinic database and analysed using SPSS and SAS. A logistic regression model was used to establish which associations with BV persisted. Results: 890 women with BV and 890 controls were studied. Factors that were independently associated with BV were ⩾3 male sexual partners in the past 12 months (OR = 1.60, 95% CI: 1.19 to 2.04), at least one female sexual partner in the past 12 months (OR = 2.1, p = 0.003), a past pregnancy (OR = 1.5, p<0.0006), and smoking. In contrast, women with BV were significantly less likely to have used hormonal contraception (OR = 0.60, 95% CI: 0.51 to 0.81) or to have used condoms consistently (OR = 0.5, 95% CI: 0.31 to 0.71) than controls. Conclusion: Our findings may be important for planning a preventive strategy for BV by discouraging smoking and increasing condom use and hormonal contraception among women.